The tax-foundation theory of fiat money - Dror Goldberg (Bar-Ilan University, Department of Economics, 2009)
A government can promote the use of an object as the general medium of exchange by accepting it in tax payments. I prove this old claim in a dynamic model and compare the mechanism to convertibility. The government can often keep its favourite money in circulation even while increasing its quantity and thus causing it to decrease in value. This opens the door for an inflationary policy. Most successful fiat moneys have been acceptable for tax payments, typically due to legal tender laws. Numerous historical failures of fiat moneys are consistent with the theory.
Keywords: 330; Papierwährung; Währungssystem; Vertragsrecht; Inflation; Dynamisches Modell; Geldtheorie